Formation of Managerial Skills of Students in the Process of Practical Training - Tojimamatovich, Jurayev Vahid (Journal of Sustainability in Integrated Policy and Practice, 2023)
In recent years, a new educational paradigm has been formed, within which the quality of modern education will be determined by the extent to which graduates of the technical school have developed competencies - the ability to identify links between knowledge and situations and apply knowledge adequately to the problems being solved. A competitive personality must have many developed qualities, such as independence, organization, the ability to solve creative tasks, design their own activities, be ready for accelerated adaptation, changes in production and social space. Therefore, one of the important forms and methods of implementing new approaches in the educational process is competence-based learning technologies.